2002
DOI: 10.1080/07315724.2002.10719220
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Low-Carbohydratevs.High-Carbohydrate Diets: Energy Restriction, Nutrient Quality and Correlation to Body Mass Index

Abstract: A study of diets of free-living adults in the U.S. showed that diets high in carbohydrate were both energy restrictive and nutritious and may be adopted for successful weight management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 16 publications
(13 reference statements)
1
12
1
Order By: Relevance
“…This finding is in contrast to previous studies, which showed an inverse association between carbohydrate consumption and BMI [24,36]. Newby et al [37] reported that those with the highest carbohydrate consumption (61.9% of energy) had the lowest annual gain in BMI and waist circumference.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…This finding is in contrast to previous studies, which showed an inverse association between carbohydrate consumption and BMI [24,36]. Newby et al [37] reported that those with the highest carbohydrate consumption (61.9% of energy) had the lowest annual gain in BMI and waist circumference.…”
Section: Discussioncontrasting
confidence: 78%
“…Newby et al [37] reported that those with the highest carbohydrate consumption (61.9% of energy) had the lowest annual gain in BMI and waist circumference. Typically, higher carbohydrate intake (59-67%) was associated with lower intakes of total energy [24,36,38]. Our study also showed that women with high carbohydrate intakes (N70%) took lower total energy compared to those with 55-70% carbohydrate intake.…”
Section: Discussionsupporting
confidence: 63%
“…An analysis from the 1994 to 1996 Continuing Survey Food Intake by Individuals by the United States Department of Agriculture considered a very low carbohydrate intake to be less than 30% of daily calories and a lowcarbohydrate intake to be 30% to 45% of daily calories [5]. A recent meta-analysis of carbohydrate restriction in diabetes management compared lower carbohydrate diets, which varied in carbohydrate content from 4% to 45% of daily calories, to control diets higher in carbohydrates [2•].…”
Section: Low-carbohydrate and Restricted-carbo Hydrate Defi Nitionsmentioning
confidence: 99%
“…The diet of early hunter-gatherers and some isolated societies contained little carbohydrate because most foods rich in carbohydrates are from cultivated crops [5,6]. Agricultural development brought about the rise of civilization and the gradual rise of carbohydrate levels in human diets.…”
Section: Evolution Of Low-carbohydrate Diets In Diabetes and Obesity mentioning
confidence: 99%
“…58 Obese children and adolescents also may have lower levels of some fat soluble vitamins (A, D and E), 59,60 and dietary calcium intake has been decreasing among children and adolescents over the past few decades. 61,62 Specific data on pre-existing calcium and vitamin D deficiencies in obese adolescents are lacking. Short-term preliminary assessment of a series of adolescents in our program is reassuring, as we have found that bone mineral content and density is typically 2 to 3 s.d.…”
Section: Nutritional Risks Of Weight Loss Surgerymentioning
confidence: 99%